Consumer responses toward green advertising: The effects of gender, advertising skepticism, and green motive attribution. Issue 4 (18th May 2020) - Yu, Jason
ABSTRACT: This research examined the effects of gender and skepticism toward advertising in general (SKEP) on consumer responses toward green advertising at two levels, generalized green advertising skepticism and personalized attitude toward the green ad (Agreen-ad ). Using survey data, Study 1 found that men were more skeptical of advertising in general then women, and in turn, more skeptical of green advertising. Study 2 analyzed some of the data collected from an experiment and provided further evidence supporting the effects by showing that women's Agreen-ad was more positive than men's because of the different levels of SKEP across gender. Through introducing and testing motive attribution as a mediator, the study also offered some insight into the mechanism of the SKEP effect on Agreen-ad, i.e., consumers with higher SKEP will more likely attribute the green ad motive to for-profit marketing tactics rather than for-environment efforts, and that in turn will generate negative Agreen-ad . Agreen-ad was diagnosed as unidimensional, but when tested separately, the utilitarian dimension was found to be more vulnerable to the effects of gender and SKEP.